Conscience Clause Laws Already Permit Secular Hospitals to Withhold or Withdraw Life-Sustaining Treatment over Surrogate Objections. - Pope, Thaddeus Mason (American Journal of Bioethics, 2026)
The article examines the legal and ethical framework allowing hospitals in the U.S. to refuse or withdraw life-sustaining treatment without surrogate consent, focusing on two exceptions: professional reasons and reasons of conscience. It highlights that while hospitals’ ability to refuse treatment for professional reasons is increasingly constrained, institutional conscience rights—already supported by federal and state laws such as healthcare decisions laws, panoramic conscience clause laws, and treatment-specific statutes—offer a distinct and expanding basis for refusal. The article discusses how secular hospitals, not just religious ones, assert conscience-based objections and emphasizes the importance of transparency and patient transfer options to mitigate potential harms from institutional refusals. It concludes that as medical standards become more contested, hospitals may increasingly rely on conscience rights to justify treatment refusals.